Synthesis, Characterization and Strengthening Mechanisms of In Situ Formed Al7Cr + Al2O3 Reinforced Aluminium Matrix Composites - Gautam G.; Kumar V.; Jaiswal A.; Sharma S.; Shukla R. (My University, 2025)
The present study outlines the contribution of various strengthening mechanisms to the yield strength of multiple reinforced aluminium matrix composites. The composite was characterized by XRD for phase identification, SEM and EDS, and TEM was used for particle distribution and morphology (shape and size). Observation showed homogenous dispersion of micron size Al7Cr particles in the matrix, while Al2O3 particles as clusters. Though the presence of Al2O3 particles was observed as pockets of clusters, the overall presence of multiple particles improved the mechanical properties of commercially pure aluminium. The strengthening mechanisms, namely grain refinement, dislocation and Orowan, are quantified for these composites and, the combination of these is in accordance with observed experimental strengths. Dislocation strengthening is the predominant mechanism in the composites, followed by Orowan strengthening, and grain refinement strengthening has the least contribution. © The Indian Institute of Metals - IIM 2025.